The Effect of Motivation, Welfare, Work Spirit and Work Engagement on the Performance of Employees at the Indonesian Aviation Academy - Santoso, Herdi; Tobing, Diana Sulianti K; Patiro, Shine Pintor Siolemba (Jurnal Informatika Ekonomi Bisnis, 2025)
This study examines the influence of motivation, welfare, work spirit, and work engagement on the performance of employees at the Indonesian Aviation Academy Banyuwangi. The research addresses a gap in existing literature by integrating these four variables within the context of a high regulation, safety critical vocational education environment. Using a quantitative approach, data were collected from 60 civil servants through a structured questionnaire employing a five point Likert scale. The variables were measured using established indicators, and the data were analyzed through validity and reliability testing, followed by regression analysis including partial, simultaneous, and coefficient of determination tests. Results indicate that all four variables have a positive and significant impact on employee performance, with work engagement emerging as the most dominant predictor. Collectively, these variables explain 69.7% of the variance in performance. The findings underscore the need for integrated human resource management strategies that simultaneously enhance motivation, ensure adequate welfare, strengthen morale, and foster engagement to optimize performance. The study contributes theoretical insights to human resource management in vocational education and offers practical recommendations for institutional policy making. Future research is suggested to explore additional factors such as organizational culture and leadership style to further enhance performance models in aviation education.